Lipid kinases PIP5Ks and PIP4Ks: potential drug targets for breast cancer - Jin, Yue; Xue, Jian (Frontiers in Oncology, 2023)
Phosphoinositides, a small group of lipids found in all cellular membranes, have recently garnered heightened attention due to their crucial roles in diverse biological processes and different diseases. Among these, phosphatidylinositol 4,5-bisphosphate (PI(4,5)P2), the most abundant bisphosphorylated phosphoinositide within the signaling system, stands notably connected to breast cancer. Not only does it serve as a key activator of the frequently altered phosphatidylinositol 3-kinase (PI3K) pathway in breast cancer, but also its conversion to phosphatidylinositol-3,4,5-triphosphate (PI(3,4,5)P3) is an important direction for breast cancer research. The generation and degradation of phosphoinositides intricately involve phosphoinositide kinases. PI(4,5)P2 generation emanates from the phosphorylation of PI4P or PI5P by two lipid kinase families: Type I phosphatidylinositol-4phosphate 5-kinases (PIP5Ks) and Type II phosphatidylinositol-5-phosphate 4-kinases (PIP4Ks). In this comprehensive review, we focus on these two lipid kinases and delineate their compositions and respective cellular localization. Moreover, we shed light on the expression patterns and functions of distinct isoforms of these kinases in breast cancer. For a deeper understanding of their functional dynamics, we expound upon various mechanisms governing the regulation of PIP5K and PIP4Ks activities. A summary of effective and specific small molecule inhibitors designed for PIP5Ks or PIP4Ks are also provided. These growing evidences support PIP5Ks and PIP4Ks as promising drug targets for breast cancer.